Crossword Puzzle Games to Enhance Students' Vocabulary Mastery - Ira Rafsanjani Shohib (Universitas Negeri Surabaya, 2024)
The first language skill that must be mastered when learning English is vocabulary. Vocabulary mastery is still lacking because their curiosity is still low and they consider learning vocabulary uninteresting and not very important in learning. This research aims to find out whether the use of the learning media